Analysis of Knowledge Needs of Young Entrepreneurs in the Era of Society 5.0 (Empirical Study of MSME Owners in the Special Region of Yogyakarta) - FEBRIANDIKA, Ivan (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: This study investigates the level of Knowledge needed by young entrepreneurs in the Special Region of Yogyakarta and the extent to which they have adopted advanced technology in their business operations. By studying the topic, this study aims to understand better how young entrepreneurs in the Special Region of Yogyakarta can better utilize the potential offered along with the issue of the era of society 5.0, as well as overcome challenges that may arise in awareness.Methodology:This empirical study used a structured questionnaire to collect data from young entrepreneurs in the Special Region of Yogyakarta. The questionnaire includes questions about their Knowledge needs to develop their business in society 5.0 to identify relevant needs in the era of society 5.0. The questionnaire is processed to determine the value of importance, type of Knowledge, and its impact on the productivity of entrepreneurs in the Special Region of Yogyakarta.Findings: The results of the questionnaire were closed and analyzed with a simple method. The results of this study were as follows: Education (Average: 3.73) The average score of knowledge needs in education is 3.73 out of a scale of 5.0.Implication:By studying the topic, this study aims to understand better how young entrepreneurs in the Special Region of Yogyakarta can better utilize the potential offered along with the issue of the era of society 5.0, as well as overcome challenges that may arise in awareness.